Unit for vibro-impact dehydration of wastes of food production in the press-form - Севостьянов, Иван Вячеславович; Слабкий, Андрей Валентинович; Полищук, Александр Васильевич; Ольшевский, Анатолий Игоревич (Technology audit and production reserves, 2015)
It is described the unit with hydro-pulse drive for a three-step vibro-impact dehydration of wastes of food production (distillery stillage, spent grains, beet pulp, barley coffee and sludge) in the closed mold. Made using the stand-prototype experimental verification of capabilities of the proposed facility showed that it could provide in comparison with the known machines for the mechanical dehydration of 10-60 % lower final moisture content of waste, compared with equipment for thermal and electrolytic dehydration in 270-920 times less power consumption, as compared with units for the implementation of chemical and biological methods – better performance of workflows. In addition, a comparison of the unit with previously developed by the author complex of multi-stage dehydration of four separate pieces of equipment, based on calculations, showed a higher efficiency of the first: 9,5 times better performance and 33 times lower power consumption of dehydration, proposed equipment has a lower consumption of materials and dimensions, high reliability and security for staff. The article also provides formulas for determining these indicators of economic efficiency of the vibro-impact systems for dehydration of wastes of food production in the closed mold.